Genome-wide comparative analysis of clinical and environmental strains of the opportunistic pathogen Paracoccus yeei (Alphaproteobacteria) - Szuplewska, Magdalena; Sentkowska, Dorota; Lasek, Robert; Decewicz, Przemysław; Hałucha, Mateusz; Funk, Łukasz; Chmielowska, Cora; Bartosik, Dariusz (Frontiers in Microbiology, 2024)
Paracoccus yeei is the first species in the genus Paracoccus to be implicated in opportunistic infections in humans. As a result, P. yeei strains provide a valuable model for exploring how bacteria shift from a saprophytic to a pathogenic lifestyle, as well as for investigating the role of horizontally transferred DNA in this transition. In order to gain deeper insights into the unique characteristics of this bacterium and the molecular mechanisms underlying its opportunistic behavior, a comparative physiological and genomic analysis of P. yeei strains was performed.Results: Complete genomic sequences of 7 P. yeei isolates (both clinical and environmental) were obtained and analyzed. All genomes have a multipartite structure comprising numerous extrachromosomal replicons (59 different ECRs in total), including large chromids of the DnaA-like and RepB families. Within the mobile part of the P. yeei genomes (ECRs and transposable elements, TEs), a novel non-autonomous MITE-type element was identified. Detailed genus-wide comparative genomic analysis permitted the identification of P. yeei-specific genes, including several putative virulence determinants. One of these, the URE gene cluster, determines the ureolytic activity of P. yeei strainsa unique feature among Paracoccus spp. This activity is induced by the inclusion of urea in the growth medium and is dependent on the presence of an intact nikR regulatory gene, which presumably regulates expression of nickel (urease cofactor) transporter genes.Discussion: This in-depth comparative analysis provides a detailed insight into the structure, composition and properties of P. yeei genomes. Several predicted virulence determinants (including URE gene clusters) were identified within ECRs, indicating an important role for the flexible genome in determining the opportunistic properties of this bacterium.